Effect of chlorhexidine incorporation on acrylic reline resins : release studies - Marcelino, Neuza Isabel Fernandes (2016)
Tese de mestrado, Medicina Dentária, Universidade de Lisboa, Faculdade de Medicina Dentária, 2015